Antibiotic Therapy for Neonatal Sepsis - Studies on epidemiology, gentamicin safety, and early adverse effects of antibiotics - Fjalstad, Jon Widding (UiT The Arctic University of Norway, 2018)
Paper 1, 2, 3 & 4 are not available in Munin. Paper 1: Fjalstad, J.W., Stensvold, H.J., Bergseng, H., Simonsen, G.S., Salvesen, B., Rønnestad, A.E. & Klingenberg, C. (2016). Early-onset Sepsis and Antibiotic Exposure in Term Infants: A Nationwide Population-based Study in Norway. Available in The Pediatric Infectious Disease Journal, 35(1), 1-6. Paper 2: Fjalstad, J.W., Laukli, W., van den Anker, J.N. & Klingenberg, C.(2013). High-dose gentamicin in newborn infants: is it safe? Available in European journal of pediatrics (2014),173, 489-495. Paper 3: Esaiassen, E., Fjalstad, J.W., Juvet, L.K., van den Anker, J.N. & Klingenberg, C. (2017). Antibiotic exposure in neonates and early adverse outcomes: a systematic review and meta-analysis. Available in Journal of Antimicrobial Chemotherapy, 72(7), 1858-70. Paper 4: Fjalstad, J.W., Esaiassen, E., Juvet, L.K., van den Anker, J.N. & Klingenberg, C. (2017). Antibiotic therapy in neonates and impact on gut microbiota and antibiotic resistance development: a systematic review. Available in Journal of Antimicrobial Chemoterapy (2018), 73(3), 569-580. Objectives: The overall aim of this thesis was to investigate different aspects of antibiotic therapy for neonatal sepsis. Material and Methods: The epidemiology of early onset sepsis (EOS) and systemic antibiotic exposure in the first week of life was studied in a nationwide population-based study from the Norwegian Neonatal Network between 2009-2011. A high-dose extended-interval gentamicin regimen was studied in the neonatal unit in Tromsø from 2004-2012. Early adverse effects of antibiotic therapy were studied in a systematic review. We included observational studies and randomized controlled trials that provided data on different categories of antibiotic therapy and either the risk of necrotizing enterocolitis, invasive fungal infection, death, antibiotic resistance development, or changes in the gut microbiota. Results: There were 0.54 cases of culture-confirmed EOS per 1000 live-born term infants ...